Physico-theology religion and science in Europe, 1650-1750 - Blair, Ann, 1961-; Greyerz, Kaspar von (Medicine, science, and religion in historical context., 2020)
"Physico-theology is a term for the innovative currents of thought in England and Europe that emphasized the religious value of the new sciences and philosophies after 1650. This term is central to the relations between science and religion during the intellectual transition from early modern to modern. This edited volume is the first publication in which experts from multiple national perspectives address the interactions of physico-theology and natural theology in England and on the Continent"--